PERBEDAAN KEMAMPUAN KOMUNIKASI MATEMATIS DAN SELF CONFIDENCE SISWA ANTARA TPS DAN STAD - Kiki Nuraeni; Ekasatya Aldila Afriansyah (Universitas Muhammadiyah Makassar, 2021)
Low communication skills and self-confidence affect student learning outcomes. Therefore, there is a need for efforts to improve students' mathematical communication skills and self-confidence, one of which is by using the Think Pair Share learning model and the Student Team Achievement Divisions. The purpose of this study was to analyze differences in mathematical communication skills and self-confidence between students who received the Think Pair Share learning model and the Student Team Achievement Divisions, learning model. The research method used was quasi-experimental with a population of all class X students of SMA Negeri 15 Garut. The sampling technique used was purposive sampling by taking a sample of two classes, namely 31 students of class XMIA-8 and 34 students of class XMIA-4. The research instruments used were essay tests and questionnaires. Based on the results of the data analysis, it was concluded that there were differences in mathematical communication skills and self-confidence between students who received the Think Pair Share learning model and the Studen Team Achievement Divisions learning model.